2021
DOI: 10.1523/jneurosci.2093-20.2021
|View full text |Cite
|
Sign up to set email alerts
|

Memory Destabilization and Reconsolidation Dynamically Regulate the PKMζ Maintenance Mechanism

Abstract: Useful memory must balance between stability and malleability. This puts effective memory storage at odds with plasticity processes, such as reconsolidation. What becomes of memory maintenance processes during synaptic plasticity is unknown.Here we examined the fate of the memory maintenance protein PKMf during memory destabilization and reconsolidation in male rats. We found that NMDAR activation and proteasome activity induced a transient reduction in PKMf protein following retrieval. During reconsolidation,… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 47 publications
2
1
0
Order By: Relevance
“…The recall of these distinct memories resulted in differential brain activation in some structures. In line with the role of the amygdala 4750 and paraventricular nucleus 51,52 in fear expression, we observed that cfos counts in these structures increased as a function of the strength of the fear memory. Conversely, in the infralimbic cortex, cfos expression was decreased in the 10S group, which is in line with its established role in safety learning and fear suppression 53,54 ).…”
Section: Discussionsupporting
confidence: 85%
“…The recall of these distinct memories resulted in differential brain activation in some structures. In line with the role of the amygdala 4750 and paraventricular nucleus 51,52 in fear expression, we observed that cfos counts in these structures increased as a function of the strength of the fear memory. Conversely, in the infralimbic cortex, cfos expression was decreased in the 10S group, which is in line with its established role in safety learning and fear suppression 53,54 ).…”
Section: Discussionsupporting
confidence: 85%
“…The recall of these distinct memories resulted in differential brain activation in some structures. In line with the role of the amygdala ( Bernabo et al, 2021 ; Gründemann et al, 2019 ; Josselyn et al, 2015 ; Maddox et al, 2019 ) and paraventricular nucleus ( Do-Monte et al, 2015b ; Padilla-Coreano et al, 2012 ) in fear expression, we observed that c-fos counts in these structures increased as a function of the strength of the fear memory. Conversely, in the infralimbic cortex, c-fos expression was decreased in the 10S group, which is in line with its established role in safety learning and fear suppression ( Bloodgood et al, 2018 ; Do-Monte et al, 2015a ).…”
Section: Discussionsupporting
confidence: 84%
“…Yet, there is still much to learn about memory processing beyond the initial encoding and consolidation phases, where memory traces are not necessarily permanent and can become labile upon reactivation [84]. Behavioural tagging experiments demonstrate that reactivated memory traces, which can occur owing to re-exposure to the trained environment or conditioned stimulus, subsequently undergo protein synthesis-dependent re-consolidation, involving PRPs such as PKMζ [85]. This requirement for protein synthesis suggests that re-consolidation could also involve STC mechanisms [11].…”
Section: (H) Behavioural Tagging: Behavioural Correlate Of Stcmentioning
confidence: 99%